Antenatal Magnesium Sulfate Exposure and Hemodynamically Significant Patent Ductus Arteriosus in Premature Infants - Amna Qasim; Sunil K. Jain; Ashraf M. Aly (Thieme Medical Publishers, Inc., 2019)
Objective The use of antenatal magnesium sulfate (MgSO4) has been associated with neuroprotective effects. One of its' proposed mechanisms of action includes antagonism of calcium channels. Calcium influx is important for closure of ductus arteriosus. We hypothesized that antenatal MgSO4 exposure may be associated with an increased risk of hemodynamically significant patent ductus arteriosus (HsPDA) in premature infants (PI). Study Design A prospective cohort study conducted in two parts. PI (< 32 weeks and < 1,500 g) were recruited (n = 105). All infants had Echocardiograph (ECHO; within 3 days) and blood samples drawn at the same time for B-type natriuretic peptide (BNP; part 1) and NTproBNP (N-terminal pro BNP; part 2) measurements. HsPDA was defined as a PDA diameter > 1.5 mm and BNP levels > 40 pg/mL or NTproBNP > 10,200 pg/mL. Infants were divided into two groups based on antenatal MgSO4 exposure. Data were analyzed using SPSS 23. Difference in baseline characteristics and antenatal steroid use in the two groups was analyzed. A matched group analysis was performed to adjust for the difference in the numbers between the two groups. A p-value < 0.05 was considered significant. Results There was no significant difference seen in baseline characteristics or use of antenatal steroids in exposed versus unexposed (n = 95 vs. n = 10). There was a significant negative correlation between antenatal MgSO4 exposure and HsPDA in PI (p ≤ 0.05). However, this association was not significant after matched group analysis. Conclusion Antenatal MgSO4 exposure is not associated with an increased risk of HsPDA. It may be associated with a decreased likelihood of HsPDA.